Loss of First Permanent Molar Teeth in Patients Attending in OPDs of Selected Dental Hospitals in Dhaka City (Bangladesh Journal of Dental Research & Education, 2015)
Teeth loss, especially first permanent molar teeth loss is the ultimate barometer of failure or success in dentistry and dental health programs. A cross-sectional study was conducted among 210 patients attending in outpatient department of selected dental hospitals in Dhaka city to find out the loss of first permanent molar teeth among them. Regarding age (34.8%) of the respondents were below 25 years followed by 25.5% between 25 35 years (mean age 33.16 ± 14.10 years). In case of educational status (31%) completed primary education followed by 16.2% were graduates and 33.3% were illiterates. Majority (59.5%) of the respondents had monthly family income below 5000 BDT (mean income 6802.39 ± 6630. 39 BDT). Among the respondents, 33.8% knew brushing technique and 79.5% of them brushed once in a day. Majority (68.5%) of them used tooth paste for brushing and tooth brush was used by 67.1% of the respondents. In case of first permanent molar tooth missing, 50% missed lower left, 19.6% lower right, 17.4% upper left and 13%  upper right. Among the respondents, 86% teeth loss was due to caries followed by periodontal disease (12.4%) and orthodontic reason (5.2%). Among the respondents who lost tooth, 55.7% were below 15 years followed by 15 - 30 years (34.3%) and above 30 years (10%). Regarding oral hygiene status, 19% had satisfactory and 81% had unsatisfactory oral hygiene. So it can be concluded that loss of permanent first molars can be avoided if good preventive measures are used before these teeth erupt and are continued after they have erupted in addition to maintaining proper oral hygiene. Further large scale study regarding this topic is recommended.Bangladesh Journal of Dental Research and Education Vol.5(2) 2015: 40-43